Membrane platform protein PulF of the Klebsiella type II secretion system forms a trimeric ion channel essential for endopilus assembly and protein secretion - Ingrid Guilvout; Firdaus Samsudin; Roland G. Huber; Peter J. Bond; Benjamin Bardiaux; Olivera Francetic (mBio, 2024)
ABSTRACTType IV pili and type II secretion systems (T2SS) are crucial for bacterial adaptation, virulence, and environmental impact. A common mechanism underlying their multiple functions involves assembly of dynamic plasma membrane-anchored filaments—the (endo)pili. The cytoplasmic ATPase motor GspE/PilB is thought to energize pilus assembly via the membrane assembly platform protein GspF/PilC, but platform protein structure and its molecular role remain elusive. Here, to dissect the GspF/PilC architecture and mechanism, we generated all-atom models of the Klebsiella T2SS platform protein PulF in different oligomeric states. Comprehensive modeling, molecular dynamics (MD) simulations, cysteine crosslinking, and biochemical analyses support the trimeric state of PulF. In the trimer, the transmembrane segment TMS2 and the nonessential cytoplasmic N-domain are peripherally located, while TMS1 and TMS3 form a 6-helix bundle delineating a central transmembrane channel. Polar and proline residue pairs in these segments, conserved in all GspF/PilC homologs, define the channel constriction that can accommodate sodium ions or protons. Remarkably, obstructing this channel via Cys crosslinking abolished endopilus assembly and protein secretion, shedding light on previous findings showing that dissipating the membrane potential with ionophores reversibly abolished T2SS function. The trimeric PulF shows an excellent fit with the PulE ATPase hexamer, building a complex with structural similarities to the V-ATPase. MD simulations of PulF inserted in an Escherichia coli membrane model reveal strong binding and enrichment in cardiolipin, the phospholipid known to stimulate ATPase activity of GspE/PilB. We propose that GspF/PilC cooperates with the ATPase to energize (endo)pilus assembly using the ion motive force.IMPORTANCEType IV pili and type II secretion systems are members of the widespread type IV filament (T4F) superfamily of nanomachines that assemble dynamic and versatile surface fibers in archaea and bacteria. The assembly and retraction of T4 filaments with diverse surface properties and functions require the plasma membrane platform proteins of the GspF/PilC superfamily. Generally considered dimeric, platform proteins are thought to function as passive transmitters of the mechanical energy generated by the ATPase motor, to somehow promote insertion of pilin subunits into the nascent pilus fibers. Here, we generate and experimentally validate structural predictions that support the trimeric state of a platform protein PulF from a type II secretion system. The PulF trimers form selective proton or sodium channels which might energize pilus assembly using the membrane potential. The conservation of the channel sequence and structural features implies a common mechanism for all T4F assembly systems. We propose a model of the oligomeric PulF—PulE ATPase complex that provides an essential framework to investigate and understand the pilus assembly mechanism.